Price Difference in Buying Fruits With Many Amount And A Little According to The Islamic Law Perspective: Case Studi at Market 26 Ilir Palembang - Rina Dwi Wulandari (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Purpose:The purpose of this article is to find out the differences in the price of fruit with large and small perspectives of Islamic law in the 26 ilir Palembang market and what factors cause the difference in fruit prices for traders in the 26 ilir Palembang market.Design/Method/Approach :A qualitative approach was applied to this study. The data collection techniques use observation, interviews, and questionnairesFindings: the difference in the price of buying and selling fruit from the perspective of Islamic law in Palembang 26 ilir is permissible (mubah), because it is in accordance with the concept of buying and selling in Islam where the fulfillment of the conditions in pricing is in accordance with the principles of buying and selling in Islam. The process of buying and selling carried out has also fulfilled the pillars and conditions in Islam, so the sale and purchase of this law is legal, and the factors that cause the price of fruit differ in fruit traders in the 26 ilir Palembang market, namely fruit quality, the effect of fertilizer increase, merchant's trading location and the number also fruit traders take fruit from other fruit sellers and resell them.Originality/Values: The main contribution of provide information to the public about differences in selling prices of fruit in the market.